Football refereeing: an integrative review - Aragão e Pina, J.; Passos, A.; Araújo, D.; Maynard, M. (Psychology of Sport and Exercise, 2018)
Objective The number of football-related studies has increased considerably in recent years, in part due to the worldwide popularity of this sport. However, in what concerns football refereeing, literature is still very scattered. Thus, the purpose of this study was to provide an updated integrative review of studies addressing refereeing within football. Design Our study is an integrative review of the football referee literature. Method Using the keywords “Soccer Referee”, “Football Referee” and “Football Association Referee,” a review was conducted through September 2016, using the Web of Knowledge and Scopus databases. Results Literature search resulted in 267 full text articles which were grouped into seven themes and 54 sub-themes. Themes and sub-themes were generated through an inductive and deductive process of data analysis. Conclusion In addition to summarising the current state of the literature, we also outline possible paths for future research on the topic of football refereeing. In fact, the results of our review suggest that there is a need to extend the scope of empirical research in refereeing to include various other topics, as well as a need to further develop theoretical models regarding the performance of football referees, which could be used in their training and development.